2005
DOI: 10.1080/08039480500213733
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in people with severe mental illness. Reliability and validity of the Manchester Short Assessment of Quality of Life (MANSA)

Abstract: The Manchester Short Assessment of Quality of Life (MANSA) is a short interview, which has received a recent interest in research investigating quality of life in people with mental illness. In the present study, the Swedish version of MANSA is examined with regard to reliability, in terms of internal consistency and construct validity. Ninety-two persons with severe mental illness were interviewed regarding quality of life, social network, psychosocial functioning, psychiatric symptoms, needs for care, empowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 16 publications
6
115
0
2
Order By: Relevance
“…It is a short version of the Lancashire Quality of Life Profile (LQLP) [27]. The Swedish version, found to be psychometrically sound [28], was used. The MANSA is administered as a structured interview and includes the individual's subjective rating of general life satisfaction as well as satisfaction concerning 11 different quality of life domains: work, economic situation, social relations, leisure, housing situation, safety, people one lives with, sexual relations, family relations, and physical and psychological health.…”
Section: Quality Of Lifementioning
confidence: 99%
“…It is a short version of the Lancashire Quality of Life Profile (LQLP) [27]. The Swedish version, found to be psychometrically sound [28], was used. The MANSA is administered as a structured interview and includes the individual's subjective rating of general life satisfaction as well as satisfaction concerning 11 different quality of life domains: work, economic situation, social relations, leisure, housing situation, safety, people one lives with, sexual relations, family relations, and physical and psychological health.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The Swedish version has obtained satisfactory internal consistency (Björkman and Svensson, 2005). MANSA is completed as a structured interview measuring different domains of life satisfaction such as health, housing, and social relationships.…”
Section: Assessment Of Health-related Variablesmentioning
confidence: 99%
“…Responses to the 11 life domain items are summarized into a composite quality of life score. The Swedish version [29], used in the present study, has shown construct validity and satisfactory internal consistency.…”
Section: Quality Of Lifementioning
confidence: 99%